Some Remarks on Professor Hansen's View on Technological Unemployment: A Rejoiner - Hansen, Alvin H. (Quarterly Journal of Economics, 1932)
Journal Article A Rejoiner Get access Alvin H. Hansen Alvin H. Hansen University of Minnesota Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 3, May 1932, Pages 562–565, https://doi.org/10.2307/1883402 Published: 01 May 1932